Pengaruh Promosi Terhadap Kepercayaan Pelanggan Dan Loyalitas Donatur Pada Yayasan Pendidikan Mentari Ilmu Karawang - Runi Nurazizah; Sungkono Sungkono (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study aims to analyze the effect of promotion and service quality on donor trust and loyalty to the Mentari Ilmu Foundation. This study used a quantitative approach with a survey method of 30 people. Measurement of variables using a Likert scale with a weight of 1 to 5. This study found that promotion has a positive and significant effect on loyalty, service quality has a positive and significant effect on loyalty, trust has a positive and significant effect on loyalty, promotion has an effect on loyalty through trust.